2020
DOI: 10.1002/jsp2.1079
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI characterization of level dependent differences in lumbar muscle size, quality, and microstructure

Abstract: Magnetic resonance imaging (MRI) is a diagnostic tool that can be used to noninvasively assess lumbar muscle size and fatty infiltration, important biomarkers of muscle health. Diffusion tensor imaging (DTI) is an MRI technique that is sensitive to muscle microstructural features such as fiber size (an important biomarker of muscle health), which is typically only assessed using invasive biopsy techniques. The goal of this study was to establish normative values of level‐dependent lumbar muscle size, fat signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Our results here and in a previous, independent study (41) suggest that diffusion characteristics differ in the paraspinal muscles as a function of spinal segment. The observation of changing mean diffusivity over the span of the lumbar spine may draw into question the assumption of spatial uniformity, however we note that spatial consistency was assumed within one spinal segment, not across the entire spine.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results here and in a previous, independent study (41) suggest that diffusion characteristics differ in the paraspinal muscles as a function of spinal segment. The observation of changing mean diffusivity over the span of the lumbar spine may draw into question the assumption of spatial uniformity, however we note that spatial consistency was assumed within one spinal segment, not across the entire spine.…”
Section: Discussionsupporting
confidence: 80%
“…The observation of changing mean diffusivity over the span of the lumbar spine may draw into question the assumption of spatial uniformity, however we note that spatial consistency was assumed within one spinal segment, not across the entire spine. Indeed, differences in IVIM parameters across the spinal segments are likely to reflect differences in structure and physiology of the paraspinal muscles from cranial to caudal, including differences in size (including the relative contribution of erector spinae vs. multifidus), tissue composition, and metabolic capacity (41)(42)(43). We also note that the IVIM parameters were generally more variable at L1 and L5, potentially due to respiratory motion at the superior extent and coil sensitivity at the inferior extent.…”
Section: Discussionmentioning
confidence: 84%
“…It has been suggested that multifidus was the primary stabilizer of the lumbar spine whereas the erector spinae helped to stabilize the lumbar spine and conveyed motion of the trunk. 57 A recent study also showed that obese patients had fatty paraspinal muscles at the upper lumbar levels and IVDD/Modic changes at the lower lumbar levels. 58 In this study, we observed that patients with LBP had more fatty infiltration in their erector spinae at L2-L3 and L3-L4 levels concomitant with milder fatty infiltration in the multifidus at the corresponding levels and spinal degeneration (severe IVDD and Modic changes) at the lower lumbar levels.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that multifidus was the primary stabilizer of the lumbar spine whereas the erector spinae helped to stabilize the lumbar spine and conveyed motion of the trunk 57 . A recent study also showed that obese patients had fatty paraspinal muscles at the upper lumbar levels and IVDD/Modic changes at the lower lumbar levels 58 .…”
Section: Discussionmentioning
confidence: 99%